Concordance Between Clinical and Laboratory Diagnosis of Abnormal Vaginal Discharge in Chilean Women - Angélica Melo; Ximena Ossa; Giselle Fetis; Lorena Lazo; Luis Bustos; Flery Fonseca-Salamanca (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract Objective To determine the concordance between the clinical diagnosis of women with abnormal vaginal discharge (AVD) and laboratory results using molecular detection and observation of the vaginal microbiota. Methods Cross-sectional study conducted in 2018 in Temuco, Chile. A total of 25 midwives from 12 health centers participated. A total of 125 women>18 years old, volunteers, were recruited. The sample of the posterior vaginal fornix was obtained by speculoscopy. Characteristics of the discharge and of the external and internal genitalia were observed. Gram staining was used to observe vaginal microbiota, blastoconidia and pseudohyphae, and polymerase chain reaction was used for the detection of Trichomonas vaginalis and Candida albicans. The Cohen kappa coefficient was used in the concordance analysis. Results Out of a total of 125 women with AVD, 85.6% consulted spontaneously and 14.4% were diagnosed clinically during a routine check-up. Absolute concordance was significant (p=0.0012), with an agreement of 13.6%. The relative concordance was significant, but fair for bacterial vaginosis (Kappa=0.21; p=0.003) and candidiasis (Kappa=0.22; p=0.001), and slight for trichomoniasis (Kappa=0.14; p=0.009). The percentage of coincidence of the diagnoses (single or mixed) by laboratory and midwives was: bacterial vaginosis 63.2% (12/19), candidiasis 36.5% (27/74), and trichomoniasis 12.5% (4/32). There was 20% coinfection. A total of 36% of the clinical diagnoses of AVD had negative laboratory tests. Conclusion The vulvovaginitis conditions candidiasis and trichomoniasis appear to be overdiagnosed, and bacterial vaginosis appears to be underdiagnosed by the clinical diagnosis when compared with the laboratory diagnosis. The low concordance obtained shows the importance of complementing the clinical diagnosis with a laboratory study of AVD, particularly in women with failed treatments and/or coinfections with unspecific and varying signs and symptoms.